Hypoxia inhibits MHC I expression and antigen presentation to escape immune surveillance - Estephan, H; Tailor, A; Parker, R; Kreamer, M; Papandreou, I; Campo, L; Easton, A; Moon, EJ; Denko, N; Ternette, N; Hammond, E; Giaccia, A (EMBO Press, 2025)
Hypoxia is a common feature of solid tumors that has previously been linked to resistance to radiotherapy and chemotherapy, and more recently to immunotherapy. In particular, hypoxic tumors exclude T cells and inhibit their activity, suggesting that tumor cells acquire a mechanism to evade T cell recognition and killing. Our analysis of hypoxic tumors indicates that hypoxia downregulates MHC I expression and its bound peptides (the immunopeptidome). Hypoxia decreases MHC I expression in an oxygen-dependent manner, mediated by the activation of autophagy through the PERK arm of the unfolded protein response. Using an immunopeptidomics-based LC-MS approach, we found a significant reduction in presented antigens under hypoxia. Inhibition of autophagy under hypoxia enhanced antigen presentation. In experimental tumors, reducing mitochondrial metabolism through a complex I inhibitor increases tumor oxygenation and both MHC I levels as well as the immunopeptidome. These data provide the molecular mechanism governing tumor immune evasion in hypoxic conditions, offering novel insights for therapeutic interventions targeting hypoxia-induced alterations in antigen presentation.